Health education interventions to promote early presentation and referral for women with symptoms of endometrial cancer - Chalong Cheewakriangkrai (2020)
Copyright © 2020 The Cochrane Collaboration. Published by John Wiley & Sons, Ltd. BACKGROUND: Diagnosis of endometrial (womb) cancer is normally made at an early stage, as most women with the disease experience abnormal vaginal bleeding, which prompts them to seek medical advice. However, delays in presentation and referral can result in delay in diagnosis and management, which can lead to unfavourable treatment outcomes. This is particularly a problem for pre- and peri-menopausal women. Providing educational information to women and healthcare providers regarding symptoms relating to endometrial cancer may raise awareness of the disease and reduce delayed treatment. OBJECTIVES: To assess the effectiveness of health education interventions targeting healthcare providers, or individuals, or both, to promote early presentation and referral for women with endometrial cancer symptoms. SEARCH METHODS: We searched CENTRAL, MEDLINE and Embase. We also searched registers of clinical trials, abstracts of scientific meetings and reference lists of review articles. SELECTION CRITERIA: We planned to include randomised controlled trials (RCTs), both individually randomised and cluster-RCTs. In the absence of RCTs we planned to include well-designed non-randomised studies (NRS) with a parallel comparison assessing the benefits of any type of health education interventions. DATA COLLECTION AND ANALYSIS: Two review authors independently evaluated whether potentially relevant studies met the inclusion criteria for the review, but none were found. MAIN RESULTS: A comprehensive search of the literature yielded the following results: CENTRAL (1022 references), MEDLINE (2874 references), and Embase (2820 references). After de-duplication, we screened titles and abstracts of 4880 references and excluded 4864 that did not meet the review inclusion criteria. Of the 16 references that potentially met the review inclusion, we excluded all 16 reports after reviewing the full texts. We did not identify any ongoing trials. AUTHORS' CONCLUSIONS: There is currently an absence of evidence to indicate the effectiveness of health education interventions involving healthcare providers or individuals or both to promote early presentation and referral for women with endometrial cancer symptoms. High-quality RCTs are needed to assess whether health education interventions enhance early presentation and referral. If health education interventions can be shown to reduce treatment delays in endometrial cancer, further studies would be required to determine which interventions are most effective.